2022
DOI: 10.1177/10711007221115185
|View full text |Cite
|
Sign up to set email alerts
|

Early Radiographic and Clinical Outcomes of a Novel, Fixed-Bearing Fourth-Generation Total Ankle Replacement System

Abstract: Background: The Cadence Total Ankle System is a 2-component, fixed-bearing fourth-generation total ankle arthroplasty (TAA) system that was introduced for clinical use in 2016. The purpose of this study was to report non–inventor, non–industry funded survivorship, radiographic and clinical outcomes, and early complications following use of this implant at a minimum of 2 years. Methods: This single-center retrospective study included patients who underwent TAA by 2 surgeons with this novel fixed-bearing system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(85 reference statements)
0
6
1
Order By: Relevance
“…Detailed analysis indicates that clinical, radiolographic ROM, implant position outcomes, and survival rate at an early-term follow-up of 2.9 years were similar to those reported with recent Cadence studies. 15,16,25,40 However, in contrast to previous reports, this study found an unanticipated serious adverse device effect of the Cadence prosthesis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Detailed analysis indicates that clinical, radiolographic ROM, implant position outcomes, and survival rate at an early-term follow-up of 2.9 years were similar to those reported with recent Cadence studies. 15,16,25,40 However, in contrast to previous reports, this study found an unanticipated serious adverse device effect of the Cadence prosthesis.…”
Section: Discussioncontrasting
confidence: 99%
“…15,16,28,40 These reported implant survival rates ranging from 93.7% to 100%, improved patient-reported outcome measures, good postoperative total arc motion (range of motion [ROM] assessed through the angle between the tibial axis and the sole of the foot) and improved coronal ankle alignment. 15,16,25,28,40 However, with the exception of the study by Kim et al, 25 all previous reports were investigated by the inventors of the prosthesis. The study reported in this article is a European, noninventor retrospective study reviewing a consecutive series of 60 Cadence TAR systems with a minimum of 2-year follow-up, focusing on clinical and radiographic outcomes and early complications.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes for this subgroup are often reported under the broader category of posttraumatic osteoarthritis, which includes patients with ligamentous origin as well. 4,6,7,12,13 Because these 2 posttraumatic ankle arthritis etiologies have different pathomechanisms, some studies have separately evaluated postfracture ankle arthritis, 2,5,19 consistent with our research question. Nieuwe Weme et al 19 reported comparable patient-reported outcome scores and survivorship between postfracture ankle arthritis and instability arthritis patients at a mean follow-up of 5 years after undergoing mobile-bearing TAA.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, the incidence of tibial lucency (21.5%) is comparable to rates reported in some other fixed-bearing implants, which range between 20.9% and 38.0%. 15,19,20 Moreover, when comparing radiolucencies reported at 2-year follow-up to 5-year radiographs, 37.5% of the radiolucencies had resolved, 37.5% were still present, and 25% had progressed but remained asymptomatic. It is unclear why the lucencies resolved in some patients and not others, and we did not observe any change in the alignment of the components or subsidence of the implants.…”
Section: Discussionmentioning
confidence: 99%